Extending the record of Antarctic ice shelf thickness change, from 1992 to 2017. Issue 2 (15th July 2021) - Hogg, Anna E.; Gilbert, Lin; Shepherd, Andrew; Muir, Alan S.; McMillan, Malcolm
Abstract: Over the past two decades, Antarctic ice shelves have retreated, thinned and suffered catastrophic collapse. In this study we extended the 25-year long record of ice shelf thickness change in Antarctica, from 2010 to 2017. In the Amundsen Sea Sector where widespread ice shelf thinning dominates the signal, a 51% slowdown in the rate of ice loss over the last 7-years can be attributed to a coincident decrease in ocean temperatures in the region since 2010. Overall, ice shelves in Antarctica have thickened by an average of 1.3 m between 2010 and 2017 as ice losses from West Antarctica are compensated by ice gains in East Antarctica and the Antarctic Peninsula, reversing the negative trend of the previous two decades. The detailed spatial pattern of ice shelf thickness change across Antarctica, demonstrates the need for future investment in high spatial resolution observations and techniques.